850. External Validation of the Methicillin-Resistant Staphylococcus aureus Bacteremia Score. (31st December 2020) - Boyle, Ellen; Dorgan, Emily; Lunowa, Cali; Molina, Kyle C; Johnson, Tanner M; miller, matthew; Huang, Misha; Fish, Douglas
Abstract: Background: Predictive scoring systems, such as the Pitt Bacteremia Score (PBS) and Acute Physiology and Chronic Health Evaluation II (APACHE-II), can optimize clinical decisions and provide adjustment for confounding among patients with Methicillin-Resistant Staphylococcus aureus bacteremia (MRSAB). The recently introduced MRSAB score demonstrated superior discriminatory ability in mortality prediction compared to APACHE-II and PBS, however external validation is lacking. Methods: Single center, retrospective cohort study of adult patients admitted to University of Colorado Hospital from 2013–2020 with initial episode of MRSAB were included. Patients transferred from an outside hospital, left against medical advice, or died/pursued comfort care within 24 hours of index culture were excluded. The primary outcome was discrimination of 30-day all-cause mortality. The discriminatory abilities of APACHE-II, PBS and MRSAB were compared using receiver operating characteristic (ROC) analysis. The sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) were analyzed, and optimal MRSAB score was identified by Youden Index. Results: Overall, 170 patients met study inclusion. The median (IQR) age was 57 (47-66) years, 69% were male, and 19% were in an ICU during blood culture collection. The most common infection sites were skin and soft tissue (41%), musculoskeletal (23%), and line-related (19%), whereas endovascular (14%) infections were less common. The median (IQR) PBS, APACHE-II and MRSAB scores were 2 (0-4), 17 (12-23), and 6.5 (3-11), respectively. Thirty-day all-cause mortality was 12.9%. ROC curve analysis revealed an area (95% CI) for the APACHE-II, PBS, and MRSAB scores of 0.84 (0.77-0.92), 0.71 (0.57-0.85), 0.79 (0.68-0.90), respectively. A threshold MRSAB score of ≥10 was identified, whereby mortality was 3.6% with MRSAB < 10, and 30% with MRSAB ≥10. A MRSAB ≥10 had a sensitivity, specificity, PPV and NPV with corresponding 95% CIs of 0.82 (0.63-0.94), 0.72 (0.68-0.79), 0.30(0.19-0.42) and 0.96(0.92-0.99), respectively. Receiver operator characteristic (ROC) curves for the prediction of 30-day mortality Conclusion: The MRSAB score is a useful predictive scoring model, with discriminatory ability comparable to APACHE-II, and excellent NPV at ≥10. Our findings support routine clinical and research application. Disclosures: matthew miller, PharmD, Allergan (Speaker's Bureau)Tetraphase (Speaker's Bureau)